ANALISIS pH, KADAR BESI DAN KANDUNGAN TOTAL COLIFORM PADA AIR MINUM ISI ULANG GALON - Kiki Kristiandi; Susi Anisah; Junardi (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Water is an important need for human survival. The water that is often used by the Sambas people is rainwater. The aim of this research isto analyze pH, iron levels and total coliforms in refillable drinking water tanks. The approach used in this research was experiments andmeasurements carried out on gallon refills of drinking water. The parameters used in this research include pH meter, iron content usingAtomic Absorption Spectrophotometry (SSA) and total coliforms using MVN. Each test carried out in this research used ANOVA withthree repetitions. The results obtained showed that the pH in the water was in a neutral condition (7.02), while the iron content was <0.037 and total coliforms were not found or were below the threshold set by the Republic of Indonesia Minister of Health Regulation No.492/Menkes/Per/IV/2010. Based on the results of this research, gallon refillable drinking water can be consumed